Aplikasi Video Parallax Menerusi Karya Fotografi "Miniatur" - Siti Fatimah, Binti Mohammed Rais. (Universiti Malaysia Sarawak (UNIMAS), 2018)
This study aims to investigate the method of effective production through a miniature photography approach to food subjects. By identifying and analyzing the methods used by the artist's reference artist to process the work through the artist's references that have been made. Successful methods will be used as a miniature photographic work through the selection of appropriate food subjects. The images that have been successfully produced will be edited into a parallax video presentation for the audience to see. The question and research questions will be investigated by the researcher to obtain information about the research to be done later.